1999
DOI: 10.1002/(sici)1097-4628(19991003)74:1<145::aid-app18>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of aqueous polycarbazole batteries

Abstract: ABSTRACT:The characteristics of electrochemically prepared polycarbazole (PCARB) as the cathode active material for secondary batteries are studied in aqueous electrolytes. The cell of the type Zn/Zn(ClO 4 ) 2 /PCARB has a specific capacity of 30 Ah/kg and an energy density of 46 Wh/kg. The coulombic efficiency is about 80 -90% and is dependent on the thickness of PCARB films. Cole-Cole plots for PCARB electrodes by impedance measurements have been obtained at different oxidation potentials as a function of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 26 publications
0
35
0
1
Order By: Relevance
“…[3][4][5] Also, several research works have demonstrated that the addition of an optimum amount of an electrolytic filler greatly enhances the ionic conductivity and affects the bulk properties of the electrolytes. [5][6][7][8][9][10] Interesting effects were observed by us on the optoelectrical properties of PS/alum composites. 5 On the other hand, the dielectric spectra and relaxation processes of electrolyte polymers and polymer electrolytes have been studied before but the dielectric properties especially the relaxation process and the estimation of relaxation time using Yan and Rhodes model for PEO/NH 4 I electrolytes have not been previously reported.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…[3][4][5] Also, several research works have demonstrated that the addition of an optimum amount of an electrolytic filler greatly enhances the ionic conductivity and affects the bulk properties of the electrolytes. [5][6][7][8][9][10] Interesting effects were observed by us on the optoelectrical properties of PS/alum composites. 5 On the other hand, the dielectric spectra and relaxation processes of electrolyte polymers and polymer electrolytes have been studied before but the dielectric properties especially the relaxation process and the estimation of relaxation time using Yan and Rhodes model for PEO/NH 4 I electrolytes have not been previously reported.…”
mentioning
confidence: 84%
“…5 On the other hand, the dielectric spectra and relaxation processes of electrolyte polymers and polymer electrolytes have been studied before but the dielectric properties especially the relaxation process and the estimation of relaxation time using Yan and Rhodes model for PEO/NH 4 I electrolytes have not been previously reported. [1][2][3][4][5][6][7][8][9][10][11][12][13] When the dielectric material is exposed to an alternating electric field that is generated by applying a sinusoidal voltage the displacement polarization leads to electric oscillations. The orientational polarization is not a resonant process, because the molecular dipoles have inertia.…”
mentioning
confidence: 99%
“…Şarj edilebilen piller, optik cihazlar, elektrolitik kapasitörler, güneş pilleri, sensör ve biyosensör çalışmaları bu materyallerin uygulama alanları arasında en iyi bilinenleridir [25][26][27][28]. Ayrıca, iletken polimerlerin elektrokimyasal olarak biriktirilmeleri kolay olduğu için elektrot yüzeyinde duyarlı bir tabakanın oluşmasını sağlamaktadırlar.…”
Section: İletken Poli̇merlerunclassified
“…The conductive and semiconducting properties of these polymers make them an important class of materials for a wide range of electronic, optoelectronic and biotechnological applications such as in rechargeable batteries, molecular electronics, electronic displays, solar cells, ion exchange membrane in fuel cells, diodes, capacitors, field-effect-transistors, printed circuit boards, chemical sensors, drug release systems and biosensors, etc. [1][2][3][4]. It is being projected that conducting polymers can be used to transport small electronic signals in the body, i.e.…”
Section: Introductionmentioning
confidence: 99%